MKK3/6-p38 MAPK signaling is required for IL-1 beta and TNF-alpha-induced RANKL expression in bone marrow stromal cells - Rossa, Carlos; Ehmann, Kathryn; Liu, Min; Patil, Chetan; Kirkwood, Keith L. (Mary Ann Liebert, Inc., 2006)
Coupled bone turnover is directed by the expression of receptor-activated NF-kappa B ligand (RANKL) and its decoy receptor, osteoprotegerin (OPG). Proinflammatory cytokines, such as interleukin-1 beta (IL-1 beta) and tumor necrosis factor-alpha (TNF-alpha) induce RANKL expression in bone marrow stromal cells. Here, we report that IL-1 beta and TNF-alpha-induced RANKL requires p38 mitogen-activating protein kinase (MAPK) pathway activation for maximal expression. Real-time PCR was used to assess the p38 contribution toward IL-1 beta and TNF-alpha-induced RANKL mRNA expression. Steady-state RANKL RNA levels were increased approximately 17-fold by IL-1 beta treatment and subsequently reduced similar to 70%-90% when p38 MAPK was inhibited with SB203580. RANKL mRNA stability data indicated that p38 MAPK did not alter the rate of mRNA decay in IL-1 beta-induced cells. Using a RANKL-luciferase cell line receptor containing a 120-kB segment of the 5' flanking region of the RANKL gene, reporter expression was stimulated 4-5-fold by IL-1 beta or TNF-alpha treatment. IL-1 beta-induced RANKL reporter expression was completely blocked with specific p38 inhibitors as well as dominant negative mutant constructs of MAPK kinase-3 and -6. In addition, blocking p38 signaling in bone marrow stromal cells partially inhibited IL-1 beta and TNF-alpha-induced osteoclastogenesis in vitro. Results from these studies indicate that p38 MAPK is a major signaling pathway involved in IL-1 beta and TNF-alpha-induced RANKL expression in bone marrow stromal cells.